Preparação do espermatozoide como fonte de variação na produção in vitro de embriões bovinos - Gonçalves, Alexander de Oliveira (2013)
The bovine in vitro embryo production (IVEP) showed a great expansion in last decades, but, various factors concours to low embryo production rates. This paper aimed to determine the influence of cryoprotector and sperm selection gradient on super recuperation rate and sperm integrity, including the rate of IVEP. The ejaculate of a bull with high FIV rates was divided; one part was frozen with 5% glycerol (GLY) and the other with 3% of ethylene glycol (EG). At sperm selection each group was centrifuged at 5000 x g/5min in discontinuous Percoll® (MP; 90 e 45%) and OptiPrep® (MO; 30 e 26%) mini gradients (600μl), forming four experimental groups: GLI/MP; EG/MP; GLI/OP e EG/OP. Motility, agglutination, recuperation rate, membrane integrity (MI), acrosome integrity (AI) and mitochondrial activity (MA) were evaluated pre- and post-sperm selection. Embryo production rates were accessed at cleavage, D7 and D8. At thawing there was no difference (P>0,05) on sperm motility (GLY - 78.6% ± 6,9 and EG - 75.7%± 5,3) and no sperm agglutination was detected. After sperm selection motility and sperm recuperation were different (P<0,05) between the groups GLY/MP; EG/MP e GLY/OP; EG/OP (82.9 ± 7.6 e 46.5 ± 13.8; 81.4 ± 9,0 and 44.3 ± 16.3 vs. 27.1 ± 4.9 e 23.1 ± 7.4; 31,4 ± 6.9 e 29.8 ± 12.4, respectively). On the other hand, there were no difference (P>0,05) between groups in sperm structural integrity after thawing and after sperm selection. The cleavage rate of GLY/MP and EG/MP groups were higher (P<0,05) than GLY/OP and EG/OP (66.1 ± 8.1 e 60.6 ± 14.2 vs. 41.6 ± 7.9 e 48.5 ± 7.5, respectively). At D7 blastocyst rates of GLY/MP group was superior (P<0,05) than GLY/MO, but similar (P>0,05) to EG/MP group, which do not differ (P>0,05) from EG/MO. At this moment only EG/MO do not differ (P>0,05) from GLY/MO. EG/MP, EG/MO and GLY/MO groups presented similar (P>0,05) embryo production rates at D8. In conclusion, the cryoprotectant do not interfere in the evaluated sperm and embryo parameters, and Percoll® mini - gradient provided better embryo production rates than OptiPrep® mini-gradient.